Occurrence of blaCTX-M-1,qnrB1 and virulence genes in avian ESBL-producing Escherichia coli isolates from Tunisia - Kilani, Hajer; Abbassi, Mohamed Salah; Ferjani, Sana; Mansouri, Riadh; Sghaier, Senda; Ben Salem, Rakia; Jaouani, Imen; Douja, Gtari; Brahim, Sana; Hammami, Salah; Ben Chehida, Noureddine; Boubaker, Ilhem Boutiba-Ben (Frontiers in Cellular and Infection Microbiology, 2015)
Avian ESBL-producing Escherichia coli isolates have been increasingly reported worldwide. Animal to human dissemination, via food chain or direct contact, of these resistant bacteria has been reported. In Tunisia, little is known about avian ESBL- producing E. coli and further studies are needed. Seventeen ESBL-producing Escherichia coli isolates from poultry faeces from two farms (Farm 1 and farm 2) in the North of Tunisia have been used in this study. Eleven of these isolates (from farm 1) have the same resistance profile to nalidixic acid, sulfonamides, streptomycin, tetracycline and norfloxacine (intermediately resistant). Out of the six isolates recovered from farm 2, only one was co-resistant to tetracycline. All isolates, except one, harboured blaCTX-M-1 gene, and one strain co-harboured the blaTEM-1 gene. The genes tetA and tetB were carried, respectively, by 11 and 1 amongst the 12 tetracycline-resistant isolates. Sulfonamides resistance was encoded by sul1, sul2 and sul3 genes in 3, 17, and 5 isolates, respectively. The qnrB1 was detected in nine strains, one of which co-harboured qnrS1 gene. The search for the class 1 and 2 integrons by PCR showed that in farm 1, class 1 and 2 integrons were found in one and ten isolates, respectively. In farm 2, class 1 integron was found in only one isolate, class 2 was not detected. Only one gene cassette arrangement was demonstrated in the variable regions (VR) of the 10 int2-positive isolates: dfrA1- sat2-aadA1. The size of the VR of the class 1 integron was approximately 250 bp in one int1-positive isolate, whereas in the second isolate, no amplification was observed. All isolates of farm 1 belong to the phylogroup A (sub-group A0). However, different types of phylogroups in farm 2 were detected. Each of the phylogroups A1, B22, B23 was detected in one strain, while the D2 phylogroup was found in 3 isolates. The virulence genes iutA, fimH, and traT were detected in 3, 7 and 3 isolates, respectively. Two